2021
DOI: 10.3390/math9030228
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Model of COVID-19 Cases Based on the Gompertz Curve

Abstract: The COVID-19 pandemic has highlighted the need for finding mathematical models to forecast the evolution of the contagious disease and evaluate the success of particular policies in reducing infections. In this work, we perform Bayesian inference for a non-homogeneous Poisson process with an intensity function based on the Gompertz curve. We discuss the prior distribution of the parameter and we generate samples from the posterior distribution by using Markov Chain Monte Carlo (MCMC) methods. Finally, we illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The precision of the estimated parameters is determined by the theoretical reasoning of Sections 2.2 and 2.3, and by the good behavior of the model against the observed data. In this sense, some studies [20,21] using Bayesian techniques, show a similar behavior in the estimates.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The precision of the estimated parameters is determined by the theoretical reasoning of Sections 2.2 and 2.3, and by the good behavior of the model against the observed data. In this sense, some studies [20,21] using Bayesian techniques, show a similar behavior in the estimates.…”
Section: Discussionsupporting
confidence: 52%
“…In addition to the works already considered about SIRD models, interested readers can find a wide variety of models for the study of the COVID-19 pandemic in the scientific literature published in the last months: using Bayesian and stochastic techniques [20][21][22], including mobility [23], confinement and quarantine [15,24], fractional models [25], and logistic models [26], among others.…”
Section: Introductionmentioning
confidence: 99%
“…The first is data on Remission times found in Lee and Wang [23] and used by Yahaya and Abba [7] and many other researchers before them. The second data is on COVID-19 Survey in Andalusia, Spain as used by Berihuete et al [24] and can be found here: https://cnecovid.isciii. es/covid19/#documentacin-y-datos and https://www.ine.es/up/9Gq4uzeUiT.…”
Section: Resultsmentioning
confidence: 99%
“…Bayesian inference has been suggested for other models to accommodate COVID-19 data, such as the Gompertz curve (Berihuete et al. 2021 ). However, the use of the Bayesian bootstrap (Rubin 1981 ) to infer input uncertainties does not seem to have been investigated so far.…”
Section: Introductionmentioning
confidence: 99%